(untitled) (Research, Society and Development, 2021)
The aim of this study was to develop and characterize flours from tilapia, pacu and carp carcasses for inclusion in food products, aiming at nutritional enrichment. Carcasses of the three species were hot smoked and later subjected to milling, resulting in flour. Analyzes of process yields, proximate composition, calcium, iron, phosphorus, fatty acids and microbiological analysis were carried out. The yields of in natura, smoked and smoking carcasses were higher for tilapia. Tilapia and carp in natura carcasses had higher moisture and crude protein values ​​than pacu carcasses. The flour made from carp carcasses had the highest crude protein content (36.15%). Pacu flour had significantly higher lipid content (26.33%) compared to tilapia and carp. 23 fatty acids were identified in the prepared flours. Those that had the greatest representation were 18:1n-9 (oleic), 16:0 (palmitic), 18:2n-6 (linoleic), 18:0 (stearic) and 16:1n-7 (palmitoleic). The flours were presented as products with a high content of crude protein, minerals (calcium, iron and phosphorus) and total lipids, in addition to having in their compositions essential fatty acids for the human diet. The microbiological analysis of the flours showed results within the limits established by Brazilian legislation. Therefore, the fishmeal obtained in this study can be used to enrich various products for human consumption.